2022
DOI: 10.1002/1878-0261.13200
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 regulates TGFβ‐induced proliferation and self‐renewal in glioblastoma stem cells

Abstract: Glioblastoma (GBM) is the most aggressive and common glioma subtype, with a median survival of 15 months after diagnosis. Current treatments have limited therapeutic efficacy; thus, more effective approaches are needed. The glioblastoma tumoural mass is characterised by a small cellular subpopulation – glioblastoma stem cells (GSCs) – that has been held responsible for glioblastoma initiation, cell invasion, proliferation, relapse and resistance to chemo‐ and radiotherapy. Targeted therapies against GSCs are c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The main biological function of NOX family proteins is to produce ROS, which can maintain the normal physiological activities of cells [ 30 ]. Oxidative stress caused by increased ROS in the body is related to a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The main biological function of NOX family proteins is to produce ROS, which can maintain the normal physiological activities of cells [ 30 ]. Oxidative stress caused by increased ROS in the body is related to a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the respiratory chain contribution to ROS synthesis, the elevation of ROS levels can be contributed to the NADPH-oxidase family (Nox) of proteins. Cancer stem cells are known to have high basal levels of ROS, and among other Nox members, NOX4, which is constitutively active in cells, is known to regulate the expression of cancer stem cell genes in glioblastoma (Garcia-Gomez et al , 2022) and promote oncogenesis in pancreatic cancer (Ju et al , 2017). On the other hand, NOX4 has been reported to act as a tumour suppressor or oncogene depending on the tumour type.…”
Section: Resultsmentioning
confidence: 99%
“…Ford and colleagues in 2020 found that CAFs-rich TC1 and MC38 tumour models hampered cancer immunotherapy efficacy, whereas NOX4 inhibition not only reversed it but also suppressed TGFβ-induced myofibroblast differentiation and normalised CAFs to quiescence [51]. Indeed, higher NOX4 expression has been observed in gallbladder CAFs [52] and primary GSCs [54], as well as is associated with poor patient survival [52,54,55]. Besides, NOX4 overexpression in normal breast epithelial cells leads to senescence, apoptosis resistance and tumorigenic transformation [56].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%